Dwor "Najrzadniejszego w Polszcze magnata" - Kowecka, Elzbieta (Warszawa : Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1991)
A monograph on the court and the life of a Magnate of Poland in the 40's, 50's and 60's of the 18th century.
Summary in English.
Includes bibliographical references (p. 282-286).
Keywords: Branicki, Jan Klemens, -- 1689-1771.; Nobility -- Poland -- Social life and customs; Poland -- Social life and customs -- To 1795.; Nobility -- Poland -- Biography; Hetmans -- Poland -- Biography